Struktur Biomolekul dan Mekanisme Aksi Vaksin Sars-Cov-2 Efektif dalam Melawan Covid-19 - Amelia Rizki Khalidah (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: The aim of this study is to deepen understanding of the structure of the vaccine against SARS-CoV-2 infection and the underlying mechanism so that its efficacy and effectiveness can be assessed. Method: used in this journal is a systematic literature review. References for this review were identified through searches of PubMed, Google Scholar, BioRxiv, MedRxiv, drug regulatory agencies, and pharmaceutical company websites. Results: Overall, all COVID-19 vaccines had high efficacy against the SARS-CoV-2 strain and were well tolerated. All vaccines appear to be a safe and effective strategy to prevent COVID-19 from getting worse. Limitations: Further research is needed to assess the magnitude of the risks of using the vaccine against its benefits in preventing SARS-CoV-2 infection. Contribution: By understanding the structure of the vaccine and its mechanism of action, it is hoped that the selection of the right vaccine can effectively suppress the pandemic.